A case of post-caesarean vesico-uterine fistula: A rare entity becoming common? - P., Pallavee; Behera, Jeetendra; Samal, Rupal (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Vesicouterine fistula (VUF) is rare, with an incidence estimated at 1-4% of all genitourinary fistulas. We report a case of VUF which was referred to our institute on the 6th postoperative day following an emergency repeat lower section caesarean section (LSCS) at 39 weeks, with complaints of hematuria and watery discharge per vaginum for further management. Patient had stable vitals with slight abdominal distension and tenderness and watery discharge per vaginum having an ammoniacal odour. USG examination showed Foley’s bulb inside uterine cavity. CT abdomen confirmed the findings and showed presence of contrast inside uterine cavity. Patient was re-operated on 9th postoperative day in concurrence with urologists. Cystoscopy showed a 2 cm size fistulous opening. Intra-operative findings revealed a fistulous track between posterior wall of bladder and uterine incision. Appropriate reparative surgery was done. Obstetricians need to be aware of this condition particularly while operating on previous caesarean sections.